High-intensity interval training and its influence on metabolic status in adults with type 2 diabetes - Torres Mejías, Jorge (2025)
Background: High-intensity interval training (HIIT) is proposed as a promising non-pharmacological treatment for cardiometabolic complications associated with non-communicable diseases such as type 2 diabetes (DM2). Objective: To evaluate the effect of high-intensity interval training using power cycling 3 days a week for 12 weeks on metabolic control parameters in adult type 2 diabetics. Method: A pre-experimental trial was conducted with a pre-post-intervention design without a control group and non-probabilistic sampling. 27 DM2 subjects performed HIIT three times a week for 12 weeks, 17 completed the protocol. The training was performed on a stationary bicycle, and the protocol was 1 minute of intense pedalling followed by 2 minutes of rest for ten repetitions. Body weight (kg), fat mass (%), fat-free mass (%), total body water (%), waist circumference (cm), blood pressure (mmHg), glycaemia (mg/dL), glycosylated haemoglobin (HbA1c %) and lipid profile (mg/dL) were determined at baseline and at the end of the intervention. Results: After the intervention, a decrease in Hb1Ac1 (p<0.01) and total cholesterol (p<0.01) was identified. Concerning body composition, fat mass (p<0.05) decreased, while total body water increased (p<0.05). Furthermore, a reduction in systolic (p<0.01) and diastolic (p<0.01) blood pressure and waist circumference (p<0.001) was identified. Conclusion: HIIT protocol could contribute to metabolic control in people with DM2. Therefore, it could be implemented to reduce cardiovascular risk in the studied population.